Mechanisms of E-Cigarette Vape-Induced Epithelial Cell Damage - Emily Auschwitz; Jasmine Almeda; Claudia D. Andl (2023)
E-cigarette use has been reported to affect cell viability, induce DNA damage, and modulate an inflammatory response resulting in negative health consequences. Most studies focus on oral and lung disease associated with e-cigarette use. However, tissue damage can be found in the cardio-vascular system and even the bladder. While the levels of carcinogenic compounds found in e-cigarette aerosols are lower than those in conventional cigarette smoke, the toxicants generated by the heat of the vaping device may include probable human carcinogens. Furthermore, nicotine, although not a carcinogen, can be metabolized to nitrosamines. Nitrosamines are known carcinogens and have been shown to be present in the saliva of e-cig users, demonstrating the health risk of e-cigarette vaping. E-cig vape can induce DNA adducts, promoting oxidative stress and DNA damage and NF-kB-driven inflammation. Together, these processes increase the transcription of pro-inflammatory cytokines. This creates a microenvironment thought to play a key role in tumorigenesis, although it is too early to know the long-term effects of vaping. This review considers different aspects of e-cigarette-induced cellular changes, including the generation of reactive oxygen species, DNA damage, DNA repair, inflammation, and the possible tumorigenic effects.